Asymmetry of muscle co-activation during the two-armed kettlebell swing: insights into neuromuscular stability - Abuwarda, Khaled; Alotaibi, Abdulazeem; Akl, Abdel-Rahman (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionBilateral asymmetry reflects strength or functional differences between dominant and non-dominant limbs, which can influence performance. Investigating asymmetry and muscle co-activation during the two-armed kettlebell swing may clarify its role in performance enhancement and injury risk. This study specifically examined co-activation and asymmetry in shoulder and trunk muscles during the exercise.MethodTwenty-four participants (age: 23.9 ± 2.5 years; body mass: 82.8 ± 8.0 kg; height: 177.8 ± 6.5 cm) were included in the study. Surface electromyography signals were recorded using a wireless EMG system and data were collected bilaterally from twelve muscles (six muscles per side: anterior deltoid, posterior deltoid, erector spinae longissimus, erector spinae iliocostalis, external oblique, and rectus abdominis). Each participant completed two trials of the two-armed kettlebell swing, with at least five repetitions.ResultsThe results showed that the shoulder co-activation index significantly increased on both sides during the float, drop, and deceleration phases (Right side: F = 35.12; p < 0.001; Left side: F = 69.80; p < 0.001). Additionally, co-activation between the erector spinae and rectus abdominis, as well as between the erector spinae and external oblique muscles, was highest during the float and drop phases (Right side: F = 165.1; p < 0.001; Left side: F = 100.08; p < 0.001). The findings revealed some asymmetry in muscle co-activation, particularly during the float phase (22.39%). However, overall asymmetrical levels remained low during the more mechanically demanding phases (propulsion, drop, and deceleration).ConclusionThe study shows clear phase-dependent muscle activation patterns, with anterior deltoid and spinal extensors leading during propulsion, and greater posterior engagement and co-activation stabilizing the float, drop, and deceleration phases. A small asymmetry appeared mainly in the float phase, while the overall asymmetry index stayed low during the more demanding phases.